Resolving Donor–Acceptor Interfaces and Charge Carrier Energy Levels of Organic Semiconductors with Polar Side Chains. (6th September 2020) - Alessandri, Riccardo; Sami, Selim; Barnoud, Jonathan; de Vries, Alex H.; Marrink, Siewert J.; Havenith, Remco W. A.
Abstract: Organic semiconductors consisting of molecules bearing polar side chains have been proposed as potential candidates to overcome the limitations of organic photovoltaics owing to their enhanced dielectric constant. However, introducing such polar molecules in photovoltaic devices has not yet resulted in higher efficiencies. A microscopic understanding of the impact of polar side chains on electronic and structural properties of organic semiconductors is paramount to rationalize their effect. Here, the impact of such side chains on bulk heterojunction overall morphology, molecular configurations at donor–acceptor (DA) interfaces, and charge carrier energy levels is investigated. The multiscale modeling approach used allows to resolve DA interfaces with atomistic resolution while taking into account the large‐scale self‐organization process which takes place during the processing of an organic thin film. The polar fullerene‐based blends are compared to the well‐studied reference system, poly(3‐hexyl‐thiophene) (P3HT):phenyl‐C61 ‐butyric acid methyl ester (PCBM). Introduction of polar side chains on a similar molecular scaffold does not affect molecular orientations at the DA interfaces; such orientations are, however, found to be affected by processing conditions and polymer molecular weight. Polar side chains, instead, are found to impact considerably the charge carrier energy levels of the organic blend, causing electrostatic‐induced broadening of these levels. Abstract : Polar ethylene glycol side chains are emerging as an alternative way to functionalize organic semiconductors. To fully harness their potential, a microscopic understanding of their impact is paramount. To this end, a multiscale modeling approach is used to investigate the impact of such side chains on molecular configurations at donor–acceptor interfaces and charge carrier energy levels.